THE MOTIF OF FREEDOM IN MARK TWAIN’S WORKS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article examines the motif of freedom in the literary works of Mark Twain, one of the most influential figures in American literature. Freedom is analyzed as a multidimensional concept encompassing physical escape, moral independence, and social justice. Through a close reading of The Adventures of Huckleberry Finn, The Adventures of Tom Sawyer, and A Connecticut Yankee in King Arthur’s Court, the study explores how Twain critiques social norms, slavery, and authoritarian systems. The article demonstrates that Twain presents freedom not merely as the absence of restraint, but as an ethical responsibility grounded in human dignity and moral choice. By combining realism, satire, and symbolism, Twain’s works offer a profound reflection on the struggle for individual and collective freedom in a flawed society.